Aortic valve regurgitation caused by blunt chest injury. Issue 5 (November 1995) - Obadia, J. F.; Tatou, E.; David, M.
Abstract : Aortic valve regurgitation is an uncommon consequence of closed chest injury. It is caused by damage to the valve apparatus (ruptured cusp) or when subadventitial rupture of the ascending aorta causes prolapse of a subjacent valve cusp. Aortic valve regurgitation was detected in 4 patients (2 men and 2 women, 30 to 65 years old) who had sustained multiple injuries in road accidents 1 week to 30 years before. Three had subadventitial rupture of the ascending aorta and one had isolated rupture of the noncoronary cusp of the aortic valve. The mechanism responsible for the damage was believed to be a consequence of multiple chest lesions (right costal flap, sternal fracture, pulmonary contusion). It is difficult to diagnose and treat aortic regurgitation in patients with multiple injuries. Three patients had repair operations and the remaining patient needed valve replacement. If aortic regurgitation is haemodynamically well tolerated, the operation should be postponed until the patients have recovered from their other injuries. The results in these 4 patients and in other reported cases indicate that operations can be performed soon after the acute phase.